Shared genetic predisposition in rheumatoid arthritis-interstitial lung disease and familial pulmonary fibrosis. Issue 5 (11th May 2017) - Juge, Pierre-Antoine; Borie, Raphaël; Kannengiesser, Caroline; Gazal, Steven; Revy, Patrick; Wemeau-Stervinou, Lidwine; Debray, Marie-Pierre; Ottaviani, Sébastien; Marchand-Adam, Sylvain; Nathan, Nadia; Thabut, Gabriel; Richez, Christophe; et al.
Despite its high prevalence and mortality, little is known about the pathogenesis of rheumatoid arthritis-associated interstitial lung disease (RA-ILD). Given that familial pulmonary fibrosis (FPF) and RA-ILD frequently share the usual pattern of interstitial pneumonia and common environmental risk factors, we hypothesised that the two diseases might share additional risk factors, including FPF-linked genes. Our aim was to identify coding mutations of FPF-risk genes associated with RA-ILD. We used whole exome sequencing (WES), followed by restricted analysis of a discrete number of FPF-linked genes and performed a burden test to assess the excess number of mutations in RA-ILD patients compared to controls. Among the 101 RA-ILD patients included, 12 (11.9%) had 13 WES-identified heterozygous mutations in the TERT, RTEL1, PARN or SFTPC coding regions . The burden test, based on 81 RA-ILD patients and 1010 controls of European ancestry, revealed an excess of TERT, RTEL1, PARN or SFTPC mutations in RA-ILD patients (OR 3.17, 95% CI 1.53–6.12; p=9.45×10 −4 ). Telomeres were shorter in RA-ILD patients with a TERT, RTEL1 or PARN mutation than in controls (p=2.87×10 −2 ). Our results support the contribution of FPF-linked genes to RA-ILD susceptibility. Contribution of TERT, RTEL1, PARN and SFTPC mutations to rheumatoid interstitial lung disease susceptibility http://ow.ly/SXEm30a98Ic